Uncontrolled Hypertension and Non-adherence to Medical Therapy in Ulaanbaatar, Mongolia - Unurjargal, Tsolmon; Sodovsuren, Naranchimeg (Central Asian Journal of Medical Sciences, 2015)
Objectives: The purposes of this study were (1) to measure non-adherence to medical therapy in a representative sample of the hypertensive population in Mongolia; (2) to identify factors influencing non-adherence to anti-hypertensive medication; and (3) to compare non-adherence to medication in the uncontrolled and controlled hypertension groups. Methods: This descriptive study was a questionnaire-based cross-sectional analysis. A random sample of 735 hypertensive patients, aged 35-64 years was selected. Arterial hypertension was defined as uncontrolled if blood pressure ≥140/90 mmHg. Non-adherence to medication was assessed using the Morisky Medication Adherence Scale with a four-item questionnaire. Results: The study sample consisted of 265 men (36.1%) and 470 women (63.9%). The mean age of participants was 53.8 ± 8.7 years. Uncontrolled hypertension was detected in 84.7% of all hypertensive subjects. We wound 68.3% of hypertensive patient’s non-adherence to medical treatment. Significant factors influencing non-adherence to anti[1]hypertensive medication among the hypertensive population in Mongolia were younger age (35-44), low family income, not having a regular doctor for hypertension control, behavior of irregular medication intake and mono-therapy. Conclusion: Non-adherence to medical treatment was significantly more common in the uncontrolled hypertension group compared with controlled the hypertension group (79.3% vs. 7.1%, p<0.001).